HANDLING GREAT HUMAN RESOURCE FOR GOOD AND GREAT SURROUNDING - Emmywati, Emmywati; Purnomo, Teguh; Fareed, Abid (Transpublika Publisher, 2024)
Human resources are undeniably one of the most critical assets for any organization. They are the backbone, the driving force behind success. These individuals possess a unique set of positive character traits that make them invaluable. Their presence within an organization paves the way for positive transformations and growth. In this paper, we aim to foster a more constructive and optimistic perspective among certain individuals within the human resources sector. It is crucial to address any tendencies of considering oneself more significant than others. This shift in perspective is vital for achieving the collective objectives of community organizations. When individuals adopt an egocentric viewpoint, it hampers the overall working culture within social organizations. It creates barriers and impedes progress in the long run. Therefore, it becomes imperative for community organization management to invest in training and empowerment initiatives for their human resources. By doing so, they ensure that their most valuable asset is equipped with the necessary skills and mindset to thrive.